The Filipino kindergarten architecture as an active tool for values education - Ong, Timothy Augustus Y.
The Filipino Kindergarten proposes a new design for educational facilities where architecture itself is an active tool for the inculcation of Filipino cultural values, specifically that of the Filipino Value System, Pamantayan, in the Filipino child. Employing the use of didactic architecture, environmental psychology, spatial intelligence, and place making theories, the Filipino Kindergarten attempts to create educational environments better attuned to the context of the Filipino culture. With the PAUW-UP Child Study Center as a pilot project, The Filipino Kindergarten highlights the importance of built form in early education and values formation, and provides a practical approach to the integration of spatial design in the early education curriculum. Ultimately, the Filipino Kindergarten aims to be a third teacher, an active tool- that through the built environment, a sense of Filipino identity is fostered in the child, cementing architecture's role in nation building alongside education.